Upaya Meningkatkan Kemampuan Mengenal Huruf Melalui Permainan Alphabetic Ladder Snake Pada Anak Usia 5-6 Tahun di RA Salafiyah Wonoyoso - Laeli, Wafi Maulida; Hidayah, Nahdiyah (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to apply the alphabet snake and ladder game in an effort to improve the ability to recognize letters in children aged 5-6 years at RA Salafiyah. Alphabet snakes and ladders is a game tool that has been modified from the numbers snakes and ladders game to the letters snakes and ladders game. The research method used is classroom action research. The method used uses the Kemmis and Taggart cycle model which consists of four stages (planning, action, observation and reflection). Data collection was carried out by observation, interviews and documentation. The results of the research show: 1) the application of the alphabet snakes and ladders game in an effort to improve the ability to recognize letters was carried out in two cycles. 2) the results of implementing the alphabet snakes and ladders game in an effort to improve the ability to recognize letters experienced a significant increase and were able to improve the ability to recognize letters at RA Salafiyah Wonoyoso. The increase in the ability to recognize letters seen from pre-action or initial ability was 35%, increased to 54% in cycle I and increased to 81% in cycle II.